Trends and Correlates of Mean Lung Dose in Patients Receiving Breast Radiotherapy in a Single Institution from 2014 to 2018. Issue 10 (October 2020) - McKenzie, E.; Razvi, Y.; Wronski, M.; Zhang, L.; Bosnic, S.; Vesprini, D.; Paszat, L.; Rakovitch, E.; Drost, L.; Yee, C.; Russell, S.; McCann, C.; et al.
Abstract: Aims: Higher mean lung dose (MLD) in breast cancer patients has been associated with pneumonitis, pulmonary fibrosis and secondary lung cancer primaries. This study examined MLD in a single institution from 2014 to 18 to assess trends in median MLD (Gy) over time and factors associated with higher MLD to determine best practices for limiting lung toxicity. Materials and methods: General linear regressions were analysed to determine significant change in median MLD over time in patients receiving conventional or hypofractionated schedules for whole breast/chest wall (WB) radiotherapy with or without sequential boost or simultaneous integrated boost, WB tangential radiotherapy only and WB locoregional radiotherapy. Univariate and multivariable linear regression analysed identified factors associated with MLD. Results: In total, 3894 patients were included in the analysis. The total median MLD across all years was 6.8 Gy in patients treated with conventional fractionation and 3.4 Gy in patients treated with hypofractionation. A significant increase in MLD was observed between 2014 and 2018 in patients receiving conventional or hypofractionation, conventional WB treatment with locoregional radiotherapy, conventional WB radiotherapy with simultaneous integrated boost and hypofractionated WB radiotherapy with sequential boost. Increased MLD was significantly correlated with lower lung volume and larger treatment volume due to locoregional radiotherapy, inclusion of a boost, chest wall treatment and reverse decubitus or supine positioning ( P < 0.0001). Conclusion: A significant increase in MLD was observed over the years in patients receiving conventional and hypofractionated radiotherapy. Techniques such as prone positioning should be considered to lower MLD, particularly for patients with predisposing pulmonary risk. Highlights: Median mean lung dose (MLD) from 2014–2018 was 6.8 Gy for conventional and 3.4 Gy for hypofractionated radiotherapy (RT). There was a significant increase in median MLD from 2014 to 2018 in both conventional and hypofractionated RT (p < 0.0001). Wide tangents, lower lung volume, boost, chest wall, conventional or locoregional RT were associated with higher median MLD. Prone positioning was significantly associated with lower median MLD than reverse decubitus and supine positioning.